2016
DOI: 10.18869/acadpub.aassjournal.4.2.49
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Interference Effect in Bandwidth and Self-Control Feedback Conditions on Relative and Absolute Timing Learning

Abstract: This study aims to better understand the effect of practice schedule and feedback providing types. In two separate experiments the contextual interference effect in bandwidth and self-control feedback conditions on relative and absolute timing learning was examined. In experiment I, the effect of contextual interference using bandwidth and self-control feedback on absolute timing learning (parameters) was studied. Results in the acquisition test showed the performance of blocked self-control and bandwidth grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The majority were female (n=64, 53%), with a median age of 61 (40-68), an average BMI of 24.39±4.16, 70.83% (n=85) were married, and 49.17% (n=59) were employed. The median OA severity in the sample was grade 3, the median level of experienced pain was 5 (3)(4)(5)(6)(7), and the BDI score was 21.23±7.16 (mild to moderate). Bivariate analysis was conducted on the above characteristics variables and BDI score to determine which variables met the requirements for linear regression analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority were female (n=64, 53%), with a median age of 61 (40-68), an average BMI of 24.39±4.16, 70.83% (n=85) were married, and 49.17% (n=59) were employed. The median OA severity in the sample was grade 3, the median level of experienced pain was 5 (3)(4)(5)(6)(7), and the BDI score was 21.23±7.16 (mild to moderate). Bivariate analysis was conducted on the above characteristics variables and BDI score to determine which variables met the requirements for linear regression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nazarinasab et al showed that 58.5% of OA patients experience mental disorders, with depression being the most prevalent [5]. Shams et al indicated that engaging in physical activities could lead to lower levels of depression in the elderly [6]. A recent study found that females are more likely to experience incident depression within 24 months after a knee OA diagnosis [7].…”
Section: Introductionmentioning
confidence: 99%